Saccade deficits after a unilateral lesion affecting the superior colliculus. Issue 12 (December 1991) - Pierrot-Deseilligny, C; Rosa, A; Masmoudi, K; Rivaud, S; Gaymard, B
Abstract : A 70 year old patient with a small haematoma largely restricted to the area of the right superior and inferior colliculi is reported. Eye movements were electro-oculographically recorded 17 and 80 days after the onset of the haematoma. At the first examination, latency of lateral reflexive visually-guided saccades was asymmetrical, both in the gap task (central fixation point switched off 200 ms before the onset of the lateral target) and in the overlap task (central fixation point remaining switched on). Furthermore, latency of leftward saccades in the overlap task was increased, and accuracy of these saccades was impaired, at both examinations. In the immobility task (fixation straight ahead while lateral targets suddenly occurred) and in the anti-saccade task (saccade made away from the lateral target), the percentages of errors (saccades made to the target) were high at the first examination, and noticeably lower at the second. These results suggest that the superior colliculus plays an important role both in the triggering and inhibition of reflexive visually-guided saccades.